Digital screw path transfer of preoperative mandibular models using CBCT and its preliminary application in mandibular fractures - WAN Youjun, ZHANG Tianyu, ZHU Bowen, ZHU Liuning, BU Shoushan, ZHUANG Hai (Kouqiang yixue)
Objective To scan and accurately reconstruct mandible models printed via fused deposition modeling(FDM) that contain screw path information, using cone-beam CT(CBCT), to achieve the digital transfer of preoperative model screw paths. Methods CBCT scans were conducted on 12 FDM-printed mandibular models(Model1 group)intended for prebending reconstruction plates. Mimics software was employed to reconstruct scanned data into mandibular models(Model2 group) and extract digital screw path information. Model2 was then compared with original models(Model0 group) in three dimensions, evaluating reconstruction accuracy through root mean square(RMS). Reconstruction parameters were optimized to enable automatic matching of Model2 with Model0, facilitating precise digital transfer of screw paths. In clinical application, this method was utilized to produce digital short-segment drilling guides, assisting in the reduction surgery of three mandibular fracture patients. Results Model2 demonstrated automatic matching with Model0, exhibiting detailed surface characteristics and clear screw path position and orientation information. The RMS was measured at (0.32±0.09)mm. Utilization of digital segmented screw path transfer guides assisted in the satisfactory reduction surgery of three patients with comminuted mandibular fractures. Conclusion CBCT scanning of FDM-printed preoperative models accurately captures screw path position and orientation information, enabling digital transfer of screw paths and providing a novel method for precise design of digital surgical guides.